Song Songs As A Means To Convey Education Messages For Early Childhood Students - Evie Destiana (Journal of Higher Education and Academic Advancement, 2024)
Songs are an integral part of learning activities in early childhood. Every part of learning in early childhood often uses songs as reinforcement in conveying messages in learning. The purpose of this study is to find out how the implementation of songs as a means of conveying educational messages for early childhood students. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of this study contain a description of the implementation of songs as a means of conveying educational messages for early childhood students. The conclusion of this study is, songs are the right means of conveying educational messages for early childhood students, because through songs educational messages will be more easily understood and remembered by children at any time.